Implementation of Reciprocal Teaching Strategy for reading comprehension skills of XII students - Kurochman, Alvinisha Arofah; Pangestuti, Fitri Endah; Sukarni, Semi; Purwanto, Heru (Jurnal Pendidikan Surya Edukasi (JPSE), 2025)
This study explores the implementation of the Reciprocal Teaching Strategy to enhance students' reading comprehension skills in Hortatory Exposition texts. Conducted as a Classroom Action Research (CAR) over two cycles in Class XII-7 at SMA Negeri 5 Purworejo during the 2023/2024 academic year, the study involved 35 students (25 females and 10 males). Data were collected through pre-tests, post-tests, observations, and documentation, analyzed using simple descriptive quantitative methods, and presented in table and chart. The findings reveal a significant improvement in reading comprehension, with average scores increasing from 63 (Cycle I) to 81 (Cycle II). This growth highlights the effectiveness of the Reciprocal Teaching Strategy, particularly when supported by interactive instructional media such as videos. The strategy's integration of predicting, questioning, clarifying, and summarizing fosters critical thinking and active student engagement, addressing challenges in understanding both explicit and implicit textual information. These results underscore the strategy’s potential for advancing reading comprehension and its applicability in 21st-century learning contexts.